Fetomaternal outcome in sickle cell hemoglobinopathy in a tertiary care centre of North Kerala, India - D’Couth, Smitha; Kalam, Suneetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pregnancy is a serious burden to women with sickle cell disease (SCD). Our centre is the only tertiary care referral centre in the public sector which caters to the districts of Wayanad and the Nilgiris which has the maximum prevalence for SCD in South India. Hence this study was conducted to assess complications in pregnancy and maternal and perinatal outcome among women with SCD. Methods: A retrospective observational study was conducted by reviewing the medical records of all the pregnant women with SCD who had delivered in the Department of Obstetrics and Gynecology, Government Medical College, Kozhikode from January 2014 to December 2016. Results: There were 72 antenatal women with SCD during the study period with a prevalence of 0.15%. 54.17% (n = 39) patients were HbSS (sickle cell anemia), 44.44% (n = 32) were HbAS (sickle cell trait) and 1.39% (n = 1) were HbS-β thalassemia trait. There was increased risk of obstetric complications like gestational hypertension (16%), preeclampsia (11.11%), eclampsia (5.56%), HELLP syndrome (4.16%), intrauterine growth retardation (38.89%), and oligohydramnios (18.06%). Medical complications observed were mainly anaemia (76.38%), vasoocclusive crisis (18.05%), acute chest syndrome (5.56%) and infections like urinary tract infection (8.33%) and pneumonia (5.56%). The incidence of low birth weight babies (56.94%), low Apgar score (14.49%) and neonatal ICU admissions (31.88%) were high. There was no maternal mortality, but perinatal mortality was high (6.94%). Conclusion: Pregnancy in SCD is associated with an increased maternal morbidity and high perinatal mortality due to obstetric and medical complications.